ANALISIS TEKNIK TOP ROPE PADA OLAHRAGA EXTREME PANJAT TEBING BAGI MAHASISWA PECINTA ALAM UNIVERSITAS DEHASEN BENGKULU - Risky, Muhammad; Apriansyah, Dolly; Asnawati, Asnawati (Educative Sportive, 2023)
The problem in this study is that the level of rock climbing ability in the Top Rope category of students who are nature lovers at the University of Dehasen Bengkulu has not known. This study aims to determine the level of rock climbing ability in the Top Rope category for nature lovers at Dehasen University Bengkulu in the 2022/2023 period. The aim of this research is to find out the top rope technique in the extreme sport of rock climbing among students who love nature at MAPALA UNIVED Bengkulu. This research is quantitative descriptive. The population in this study were 55 Nature-loving Students at Dehasen University Bengkulu with a sample of 10 people who took the rock climbing division at Dehasen University Bengkulu Nature-loving Students. Data collection was carried out by tests and direct observation. Data analysis was carried out using the Rock Climbing Ability Assessment Norms for the category of wall climbing speed scores according to Jim. The results of this study showed that the level of rock climbing ability in the top rope category of Dehasen University Bengkulu students who took the rock climbing ability test in the top rope category was in the "good" category, which was 30%.